THE ROLE OF TRADITIONAL DIETS VS. MODERN FAST FOODS IN ADOLESCENT HEALTH IN DHANBAD: A COMPARATIVE STUDY - Prabha, Chandra; Verma, Chanchala (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Abstract: Dhanbad, often referred to as the "Coal Capital of India," is a city in Jharkhand that has seen rapid urbanization and economic growth in recent decades. This development has brought about significant changes in the lifestyle and dietary habits of its residents, particularly among adolescents. Traditionally, the diets in Dhanbad have been rooted in locally sourced, nutrient-rich foods, reflecting the agricultural heritage of the region. However, with increasing exposure to global food culture, there has been a marked shift toward the consumption of modern fast foods, which are often calorie-dense and low in essential nutrients. This comparative study aims to investigate the impact of this dietary transition on the health of adolescents in Dhanbad, focusing on the differences between traditional diets and modern fast foods. This study would look at the reason and factor behind changing food habits among the youth.